(untitled) - Ginsberg, Leon; Nackerud, Larry (Boston, 2004)
Includes bibliographical references and index; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Human biology; Social workers; Sinh lý học người; Người làm công tác xã hội; Social medicine; Y học xã hội